DESAIN PLTS ATAP MENGGUNAKAN HELIOSCOPE BERBASIS WEB PADA SMA NEGERI 3 MALINAU - wiwi anjarani; Abil Huda; Fitriani Said (Politeknik Harapan Bersama Tegal, 2023)
SMA Negeri 3 Malinau has a very large consumption of electrical energy from various loads such as lights, air conditioners, computers, printers, and other contact loads. Therefore, in its development, SMA NEGERI 3 Malinau plans to install a rooftop PLTS (Solar Power Plant) to help supply its own electric power. This study aims to design a PLTS ON Grid system on the roof of SMA Negeri 3 Malinau using a WEB-based helioscope. The PLTS design for the ON Grid system uses 160 ICA Solar modules with a capacity of 310 W and 3 Growwatt Inverters with 1 capacity of 15 kW and 2 capacity of 13 kW. After direct observation, the data was analyzed and calculated, the result was that the ON Grid PLTS system was capable of generating 63.36 MWh of electricity per year with a load of 57.28 MWh per year.